Pengelolaan Kurikulum Program Studi Pendidikan Guru Sekolah Dasar Pada Perguruan Tinggi - Sri Setyaningsih (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2016)
Generally, this study aimed to describe the curriculum management study program Elementary School Teacher in Higher Education. The specific objective of this study to describe the planning, implementation and evaluation of curriculum type of qualitative research based approach. The location or background of this research are two colleges in Hyderabad and one college in Surakarta. The data source is a research university leaders, faculty, and students of Elementary School Teacher research site. Data collection techniques, participant observation, in-depth interviews and document study. The results of the research, curriculum management organization of Primary School Teacher Education, related to the planning, implementation, and evaluation. Curriculum planning Elementary School Teacher each college has a trademark in accordance with the vision and mission. Implementation of the curriculum with regard Kridit Semester System load varies at each college. Evaluation of the curriculum is based on the potential and dynamics of each perguruang high.